Intensidade luminosa na formação de mudas de Myrciaria glazioviana (Kiaersk.) G. Barroso e Sobral e Plinia rivularis (Cambess.) A. D. Rotman - Rezzadori, Adriana Dallago (2021)
The cabeludinha (Myrciaria glazioviana) and the guapuritizeiro (Plinia rivularis) are fruit trees native to Brazil and belong to the Myrtaceae family, which produce fruits that can be consumed in natura or processed in the form of jams, jellies, yoghurts, drinks. They can also to be used in the cosmetics and pharmaceutical industries, due to the levels of antioxidants present in the fruits. However, even with potential for commercialization and use, these fruit species are historically neglected and there are practically no seedling offers available to the producer. Thus, it is necessary to seek new studies to improve knowledge with these two species. The objective of this study was to evaluate the effect of different light intensities on the formation of cabeludinha and guapuritizeiro seedlings. The work was carried out at Universidade Tecnológica Federal do Paraná - Câmpus Dois Vizinhos. The cabeludinha and guapuritizeiro seedlings from seeds were transplanted in 20-liter pots and placed in different shading structures. The experimental design was in completely randomized blocks, with a 5 x 4 factorial scheme (shading level x season), with 4 repetitions of 5 plants per experimental unit. The treatments were according to the shading levels, which are, full sun, 50% shading with black screen, 80% shading with black screen, 35% red photoconverter screen and 35% shading with black screen. The analyzed growth variables were total shoot length, stem diameter, stem length, number of shoots, shoot length, number of leaves, total chlorophyll, fresh and dry mass of shoot and root, total length of the plant, root length, trunk diameter, number of secondary roots, volume of the root system, leaf área and Dickson´s quality index. Data on temperature, relative humidity, light intensity and rainfall during the period were obtained. After two years of evaluation, the seedlings were transplanted to the field, proceeding with analysis of survival and percentage of leaves burned by the sun and fallen at 20 days. The data obtained were submitted to the Lilliefors normality test, the transformed means or not were subjected to analysis of variance and to the Duncan test (α = 0.05). For the formation of cabeludinha seedlings, it is possible to use a screened environment with any shade, the only exception of which is full sun. For guapuritizeiro the environments had no effect on the formation of seedlings, with only particularities in certain seasons of the year to increase some variables. The seedlings conducted in the field after transplantation, showed good adaptability and survival regardless of the shade condition in which they were formed.